Bursty Traffic Simulation by ON - OFF Model - Žvironienė, A.; Navickas, Z.; Rindzevičius, R. (Elektronika ir Elektrotechnika, 2006)
The proposed generation methodology of the bursty traffic has been created using the special combination of convolutions of Moore and Mealy automata. This model permits modeling of the bursty traffic using the various probabilistic distributions or their combinations. Executing the statistical researches with programs SAS and Statgraphics and establishing the traffic parameters, later this traffic may be successfully applied for the telecommunication networks modeling. ll. 4, bibl. 5 (in English; summaries in English, Russian and Lithuanian).